Prevalence, characteristics, and risk factors of non-alcoholic fatty liver disease in North East of Iran: a population-based study - Mina AkbariRad; Masoud Pezeshki Rad; Hadi Nobakht; AmirAli Moodi Ghalibaf; Abdollah Firoozi; Ashkan Torshizian; Amir Reza Bina; Ali Beheshti Namdar; Masoumeh Sadeghi (BMC Gastroenterology, 2024)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is a common dietary disorder caused by fatty changes in the liver parenchyma and hepatocytes without alcohol consumption. The present study aimed to investigate the prevalence, characteristics, and risk factors of NAFLD in the Mashhad Persian Cohort Study population. Method The present population-based cross-sectional study included all PERSIAN Organizational Cohort study in Mashhad University of Medical Sciences (POCM), Mashhad, Iran by census sampling method. Eligible participants were divided into two groups due to their NAFLD condition (NAFLD positive or NAFLD negative). All enrolled participants were evaluated based on their clinical aspects, anthropometric measures, laboratory tests, and ultrasound features. Statistical analysis was conducted using SPSS software version 16 (SPSS Inc., Chicago, USA –version 16). A P-value less than 0.05 was considered as the significance level. Results A total of 1198 individuals were included in the study, of which 638 (53.3%) were male and the rest were female. The mean age of the participants was 46.89 ± 8.98 years. A total of 246 patients (20.53%) were NAFLD positive, of which 122 (49.59%) were in grade 1, 112 (45.52%) were in grade 2, and 12 (4.87%) were in grade 3. The prevalence of fatty liver was significantly higher in males than in females (p < 0.001). There were significant differences between NAFLD positive and NAFLD negative participants in terms of having a history of hypertension (P = 0.044), body mass index (P < 0.001), body fat percentage (P = 0.001), waist circumference (P < 0.001), liver craniocaudal length (P = 0.012), fasting blood sugar (FBS) (P = 0.047), aspartate aminotransferase (AST) (P = 0.007), and alanine aminotransferase (ALT) (P = 0.001). Further analysis revealed a strong significant association between BMI, previous history of hypertension, higher levels of serum ALT, and NAFLD (P < 0.05). Conclusion It can be concluded that ultrasound findings accompanied by laboratory AST and ALT level enzymes could be a cost-benefit approach for NAFLD early diagnosis. The craniocaudal size of the liver could be a beneficent marker for estimating the severity of the disease; however, more studies are recommended to evaluate this variable for future practice against the issue.